The Evolution of Ecuadorian public administration in the period 2020–2025: A review of the Latin American scientific literature - Ruiz González, Iván (International Journal of Studies in Administrative Sciences STRATEGOS, 2026)
Public administration plays a fundamental role in the functioning of the State, as it is responsible for implementing public policies, managing collective resources and guaranteeing the provision of services to citizens. In recent years, Ecuador has experienced institutional, economic and administrative transformations that have influenced the structure and performance of its public sector. In this context, the present study analyzes the evolution of Ecuadorian public administration between 2020 and 2025 through a systematic review of Latin American scientific literature. The research was conducted using the PRISMA 2020 methodological framework and the PISCO approach to structure the search and selection process. Scientific publications were identified in regional academic databases, particularly SciELO and Latindex. After applying inclusion and exclusion criteria, fifteen studies related to public administration, state management, public policy and institutional reforms in Ecuador were selected for the final analysis. The results reveal that the literature focuses mainly on five thematic areas: institutional transformations of the State, management of public enterprises and state assets, fiscal governance and public finance, transparency and regulatory frameworks, and administrative modernization through digitalization. The studies also highlight fiscal constraints, organizational challenges and debates about the role of the State in economic and administrative governance. In conclusion, the findings indicate that Ecuadorian public administration is undergoing a complex transition characterized by institutional restructuring, fiscal limitations and emerging modernization efforts aimed at improving transparency, efficiency and digital public services.